P1-S2.72 Predictors of HSV-2 seroprevalence and willingness to accept a prescription for suppressive therapy among recently incarcerated women. (10th July 2011) - Roth, A; Van Der Pol, B; Reece, M; Dodge, B; Zimet, G
Abstract : Background: HSV-2 seropositivity has direct links with one's increased risk for HIV acquisition. Given that increases in HIV incidence are highest among women of colour in the USA, they may benefit from HSV-2 control efforts. We evaluated the acceptability of a community-based HSV-2 screening program for women in the justice system and assessed factors related to HSV-2 positivity and willingness to accept a prescription for suppressive therapy. Methods: As part of a larger randomised controlled trial, recently arrested women were recruited from a community court handling lower-level misdemeanour cases, including prostitution, in a large Midwestern city. Individuals completed an interviewer administered survey assessing factors related to HSV-2 screening intentions and were offered no-cost of point-of-care HSV-2 testing. Individuals screening positive were offered low-cost (4) suppressive therapy. Results: Participants included 136 women, 18−62 years old (median=31) with reported ethnicities of White (51%), Black (43%) and other (6%). Most (51%) had less than a high school education, were unemployed (68%) and 28% were currently facing prostitution charges. The majority (64%) of participants accepted testing and 60% tested HSV-2 seropositive. Factors associated with an infection included age (OR=1.09; 95% CI 1.03 to 1.16), Black race (OR=50.06; 95% CI1.1.70 to 1472.14), lower educational attainment (OR=5.86; 95% CI 1.13 to 30.37), current genital symptoms (OR=6.5; 95% CI 1.25 to 34.17), and lifetime number of sexual partners (OR=102.33; 95% CI 6.62 to 1581.73). Being recently arrested for prostitution was not associated with an HSV-2 diagnosis. The majority of women testing positive (84.6%) accepted a prescription for suppressive therapy. Conclusion: We detected very high rates of HSV-2 among recently incarcerated women, especially among Black women. Nearly all women who tested positive accepted a prescription for Acyclovir, indicating they were interested in suppressive therapy which could provide some benefit in preventing HIV acquisition. These results highlight how non-traditional public health partnerships, like academic-judicial system collaborations, provide an opportunity for STD control programs to intervene with high-risk individuals.